(3aUd aj JMQje GdSeGY hYbjOIs - (3LeGd GdOjf CHh GdaVd eMeO Hf CHj GdaVd Hf RjO GdKYdHj GdOhGej GdNWjHs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd GdTjN LeGd GdOjf CHh GdaVd GdNWjH jheFP HeOjfI OeTb GdeMQhSI SCdfi HYV CUMGHi Yf YbjOI Cgd GdMb hYf bhe jQbUhf hjZfhf hjReQhf hjNGdWhf GdfSGA GdGLGfH s
(3BNQgG (B:s
( (3GdejcQhajde ZjQ hGVM ai GdJUhjQ (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs